2019
DOI: 10.1111/bjh.16358
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint inhibitors in AML: are we there yet?

Abstract: Immunotherapy is distinct from traditional chemotherapy in that it acts on immune cells rather than cancer cells themselves. Monoclonal antibodies targeting immune checkpoints on T cells -CTLA-4 and PD-1and PD-L1 on the cells of immune microenvironment are now approved for clinical use in several solid tumors and hematological malignancies. This article provides a general overview of the use of checkpoint inhibitors in hematologic malignancies with a special focus in acute myeloid leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 88 publications
2
28
0
Order By: Relevance
“…Programmed cell death ligand 1 ( PD-L1) as a newly found immunoregulatory molecule, interacting with its receptor, PD-1, inhibits cytotoxic immune response and exerts antitumor immune response (37)(38)(39). The emergence of ICPI has also changed some tumors' treatment and has become a split-new standard of therapy (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Programmed cell death ligand 1 ( PD-L1) as a newly found immunoregulatory molecule, interacting with its receptor, PD-1, inhibits cytotoxic immune response and exerts antitumor immune response (37)(38)(39). The emergence of ICPI has also changed some tumors' treatment and has become a split-new standard of therapy (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…We identify T cell responses against AML, and as induction of PDL1 upregulation on tumor cells by T cell-derived IFNγ (Garcia-Diaz et al, 2017;Spranger et al, 2013) is a key cancer immunoevasion mechanism in a wide variety of cancers (Sun et al, 2018), we examine PDL1 expression on AML cells. Although it has previously been shown that IFNγ can induce PDL1 expression in AML patient samples (Berthon et al, 2010;Kronig et al, 2014), the clinical importance of this checkpoint molecule in AML remains controversial (Antohe et al, 2020;Berthon et al, 2010;Chen et al, 2008;Ghosh et al, 2020;Salih et al, 2006;Tamura et al, 2005). We demonstrate here that PDL1 expression levels on AML cells are dynamic during disease progression and that the highest expression is seen among terminally differentiated AML cells.…”
Section: Introductionmentioning
confidence: 58%
“…This is due to low immunogenicity of AML compared with solid tumors such as melanoma and NSCLC that are more immunogenic due to higher mutation rates ( 78 ). Cancer cells with higher mutation rates demonstrate increased odds of presenting antigens recognized by T cells as non-self ( 79 ), resulting in better response to immunotherapy ( 80 82 ). Furthermore, the bone marrow niche where AML and MDS tumor cells reside has a protective immunosuppressive microenvironment ( 83 , 84 ).…”
Section: Activation Of Antileukemic T Cellsmentioning
confidence: 99%